2012
DOI: 10.1038/aps.2012.39
|View full text |Cite
|
Sign up to set email alerts
|

siRNA against plasminogen activator inhibitor-1 ameliorates bleomycin-induced lung fibrosis in rats

Abstract: Aim: Plasminogen activator inhibitor-1 (PAI-1) is involved in the progression of pulmonary fibrosis. The present study was undertaken to examine the effects on pulmonary fibrosis of silencing PAI-1 expression with small interfering RNA (siRNA) and to assess the possible underlying mechanisms. Methods: Male Wistar rats were subjected to intratracheal injection of bleomycin (BLM, 5 mg/kg, 0.2 mL) to induce pulmonary fibrosis. Histopathological changes of lung tissue were examined with HE or Masson's trichrome st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 32 publications
2
27
0
Order By: Relevance
“…We (12,13,15) and others (28) have demonstrated that mitigation of ATII cell apoptosis occurs via inhibition of PAI-1, which is otherwise induced during fibrosing lung injury. These observations support the contention that the well established pro-fibrogenic effect of increased PAI-1-mediated ATII cell apoptosis can be prevented by the protection of ATII cells during lung injury using PAI-1 inhibitors (siRNA or chemical inhibitors), as reported by multiple laboratories, including ours (12,13,15,19,28,56,57). The role of PAI-1 in the regulation of fibroblast expansion, viability, and matrix deposition has been less well studied in the context of fibrosing lung injury, which is a basis for this report.…”
Section: Discussionsupporting
confidence: 83%
“…We (12,13,15) and others (28) have demonstrated that mitigation of ATII cell apoptosis occurs via inhibition of PAI-1, which is otherwise induced during fibrosing lung injury. These observations support the contention that the well established pro-fibrogenic effect of increased PAI-1-mediated ATII cell apoptosis can be prevented by the protection of ATII cells during lung injury using PAI-1 inhibitors (siRNA or chemical inhibitors), as reported by multiple laboratories, including ours (12,13,15,19,28,56,57). The role of PAI-1 in the regulation of fibroblast expansion, viability, and matrix deposition has been less well studied in the context of fibrosing lung injury, which is a basis for this report.…”
Section: Discussionsupporting
confidence: 83%
“…Importantly, clinical data demonstrated a reduction in plasma levels of PAI-1 which was observed after 4 weeks of irbesartan therapy in patients with metabolic syndrome [31]. Additionally, the progression of pulmonary fibrosis induced by BLM in rats was attenuated by administration of PAI-1 small interfering RNA [32]. Therefore, PAI-1 is an important factor attributed in lung fibrosis.…”
Section: Discussionmentioning
confidence: 98%
“…The benefit of a delivery vehicle for pulmonary administration of siRNA has been a subject of controversial discussion. In different pre-clinical models, a successful delivery in the respiratory tract of siRNA in the absence of a nanocarrier has been documented [33][34][35]. Moreover, promising results were obtained upon inhalation of free siRNA in human clinical trials for the treatment of patients infected with respiratory syncytial virus [36].…”
Section: Discussionmentioning
confidence: 99%